Statistical Analysis, Modeling and Optimiziton of Silica, Rubber Ratio and Sulfur Levels in Truck Tire Tread Compound - Atashi, H.; Shiva, M. (Asian Journal of Chemistry, 2010)
A Box-Behnken response surface approach has been made to study the possibility of decrease of natural rubber/butadiene rubber ratio in truck tire tread compound with the assistance of silica/silane reinforcement filler. A mathematical modeling has been carried out to investigate the dependency of tear resistance, crack growth, abrasion, resilience, hardness and curing properties on NR/BR ratio, silica/N330 ratio and sulfur levels. The governing mechanisms have been discussed in details with the help of statistical results and surface plots. Improvement effect of silica on tear and crack growth behaviour has been attributed to the lower filler-rubber interactions in silica filled domains that led to less elastic input energy and more consumption of input energy via hysteresis deformations. But a significant drop in abrasion and hardness has been observed in silica substituted compounds, However, when content of BR increases, the negative effect of silica on abrasion decreases. The significant effects of sulfur are the drop in the tear and crack growth resistance. On the other hand, in high silica domains increase of sulfur content has no significant negative effect on tear and crack growth. An optimum formulation with lower ratio of NR/BR in presence of silica has been calculated.